SOCIOECONOMIC IMPACT OF COVID-19 PANDEMIC ON SMALL BUSINESSES IN LAHORE - Muhammad Fayyaz Khokhar; Professor Liu Bangfan; Tayyaba Zia (International Journal of Contemporary Issues in Social Sciences, 2024)
In the economies of developed countries small and informal businesses have been widely studied and paid attention however, in the less developed countries only small attention has been paid. It also constitutes the current body of literature regarding the small business of developing countries. This study focused on the SME sector of Pakistan with a special focus on small & informal businesses particularly. In the scenario of Pakistan, there is insufficient knowledge on this sector and this research attempts to fill this gap. The total business establishment in Pakistan is comprised of more than 90 percent representation of small businesses. Dynamic and flexible Small businesses are playing their part in overcoming unemployment, increasing social capital, enhancing management skills and technology diffusion in all over Pakistan. SMEs are efficiently mobilizing domestic resources and create employment opportunities. After the examination of the problem statement, significance of the research work, and the development of the questionnaire, the researcher collected the relevant data to reach a meaningful conclusion. This study tries to discover the importance and socioeconomic impacts faced by the small business sector during the COVID-19 pandemic in Pakistan and emphasized the need to take the appropriate policy measures required to rescue the small business in post-disaster settings.